К ЮБИЛЕЮ ПРОФЕССОРА ГУЗЕВОЙ ВАЛЕНТИНЫ ИВАНОВНЫ - Гузева, Оксана Валентиновна; Гузева, Виктория Валентиновна; Разумовский, Михаил Анатольевич; Охрим, Инна Владимировна (Children’s Medicine of the North-West, 2024)
К ЮБИЛЕЮ ПРОФЕССОРА ГУЗЕВОЙ ВАЛЕНТИНЫ ИВАНОВНЫ